TEMPERATURE PREDICTION IN HOT TAPPING PROCESS FOR HIGH PRESSURE PIPELINE - ROSMAN, MUHAMMAD AIZADT (IRC, 2017)
Welding onto an in-service pipeline during hot tapping process are extremely risky and require thorough preparation and precautions, where the probability of occurrence of occupational hazards and injuries are high. Since the increase in surrounding temperature inside the working system are unpredictable, the internal pipe wall temperature and the process fluid temperature inside the pipe are unknown during operation. Therefore, this project is conducted to i) predict inner pipe wall temperature and ii) to estimate temperature of the process fluid inside the pipeline during in-service welding and iii) to construct relevant methodology and reference chart in predicting internal fluid temperature by using existing information from wall temperature chart provided by PTS 31.38.60.10 “Hot-Tapping on Pipelines, Piping and Equipment”.